$A$-transform of Wavelet Frames - Shah, F. A.; Sheikh, N. A. (Communications in Mathematics and Applications, 2012)
In this paper, we introduced the concept of $A$-transform $A = (a_{p,q,j,k})$ and study the action of $A$ on $f\in L^2(\mathbb{R}^+)$ and on its wavelet coefficients. Further, we also establish the Parseval frame condition for $A$-transform of $f \in L^2(\mathbb{R}^+)$ whose wavelet series expansion is known.